HLA haplotype frequencies and diversity in patients with hemoglobinopathies - Graziana M. Scigliuolo; Wahid Boukouaci; Barbara Cappelli; Fernanda Volt; Monica M. Rivera Franco; Nathalie Dhédin; Regis Peffault deLatour; Christine Devalck; Jean‐Hugues Dalle; Martin Castelle; Olivier Hermine; Marie Ouachée Chardin; et al. (eJHaem, 2023)
Abstract The genetic diversity of the human leukocyte antigen (HLA) system was shaped by evolutionary constraints exerted by environmental factors. Analyzing HLA diversity may allow understanding of the underlying pathways and offer useful tools in transplant setting. The aim of this study was to investigate the HLA haplotype diversity in patients with sickle cell disease (SCD, N = 282) or β‐thalassemia (β‐Thal, N = 60), who received hematopoietic cell transplantation (HCT) reported to Eurocord and the Société Francophone de Greffe de Moelle et de Thérapie Cellulaire (SFGM‐TC). We identified 405 different HLA‐A‐B‐DRB1 haplotypes in SCD and 108 in β‐Thal patients. Using data from African and European populations of the “1000 Genomes Project” for comparison with SCD and β‐Thal, respectively, we found that the haplotypes HLA‐A*30‐B*14‐DRB1*15 (OR 7.87, 95% CI: 1.66–37.3, pb = 0.035), HLA‐A*23‐B*08 (OR 6.59, 95% CI: 1.8–24.13, pb = 0.023), and HLA‐B*14‐DRB1*15 (OR 10.74, 95% CI: 3.66–31.57, pb = 0.000) were associated with SCD, and the partial haplotypes HLA‐A*30‐B*13 and HLA‐A*68‐B*53 were associated with β‐Thal (OR 4.810, 95% CI: 1.55–14.91, pb = 0.033, and OR 17.52, 95% CI: 2.81–184.95, pb = 0.011). Our results confirm the extreme HLA genetic diversity in SCD patients likely due to their African ancestry. This diversity seems less accentuated in patients with β‐Thal. Our findings emphasize the need to expand inclusion of donors of African descent in HCT donor registries and cord blood banks.